Some Factors Trigger Increasing Foodborne Diseases Cases of Livestock Origin - Kusumaningsih, Anni (Indonesian Bulletin of Animal and Veterinary Sciences, 2012)
Food is an essential need for various human body activities. Consequently, food must be guaranteed to be free from biological, chemical, and physical contaminants and other hazardous substances that can obstruct health. The presence of various hazardous contaminants in food may result in the appearance of foodborne diseases, i.e. human diseases spread through contaminated food and drinks. Biological contaminants in food can be bacteria, viruses, parasites, moulds, or fungi. The most dangerous biological contaminants that may cause an epidemic disease in human are pathogenic bacteria such as Salmonella spp., Escherichia coli, Bacillus anthracis, Clostridium spp., Listeria monocytogenes, Campylobacter spp., Vibrio cholerae, Enterobacter sakazakii, Shigella, etc. Researchers believe that there are several factors that can be the trigger that increase of foodborne diseases cases such as community demography by increasing the individual groups that are more susceptible to pathogenic foodborne infections, human behaviour related to the changes in the community life style and consumption, the advances in industrial and technological sectors through the increase of large scale food industries concentrated in one location, the global trade or travel, and increasing bacterial resistances against antimicrobials as the result of the increasing the uses of antimicrobials for disease prevention and cure in animals and humans. Key words: Factors trigger, foodborne diseases, contaminants, livestock, food